2017
DOI: 10.1007/s00894-017-3441-6
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydroisoquinolines functionalized with carbamates as selective ligands of D2 dopamine receptor

Abstract: A series of tetrahydroisoquinolines functionalized with carbamates is reported here as highly selective ligands on the dopamine D2 receptor. These compounds were selected by means of a molecular modeling study. The studies were carried out in three stages: first an exploratory study was carried out using combined docking techniques and molecular dynamics simulations. According to these results, the bioassays were performed; these experimental studies corroborated the results obtained by molecular modeling. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In previous studies of chemical reactions of interest in the zeolite chemistry, we demonstrated the usefulness of quantum theory of atoms in molecules (QTAIMs) analysis and the relevance of the information that can be obtained through the analysis of electron density distribution. One of the advantages of the QTAIM methodology over other global measures of the interaction energy is that it allows one to decompose the interaction energy in contributions by an atom or a group of atoms, and because of which it was used in the analysis, design, and optimization of ligand molecules in the ligand/receptor recognition process . Similar analysis could be applied in the study of adsorbate–catalyst interactions, which makes it particularly useful for these catalytic systems where several interactions are found.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In previous studies of chemical reactions of interest in the zeolite chemistry, we demonstrated the usefulness of quantum theory of atoms in molecules (QTAIMs) analysis and the relevance of the information that can be obtained through the analysis of electron density distribution. One of the advantages of the QTAIM methodology over other global measures of the interaction energy is that it allows one to decompose the interaction energy in contributions by an atom or a group of atoms, and because of which it was used in the analysis, design, and optimization of ligand molecules in the ligand/receptor recognition process . Similar analysis could be applied in the study of adsorbate–catalyst interactions, which makes it particularly useful for these catalytic systems where several interactions are found.…”
Section: Introductionmentioning
confidence: 97%
“…22−25 One of the advantages of the QTAIM methodology over other global measures of the interaction energy is that it allows one to decompose the interaction energy in contributions by an atom or a group of atoms, and because of which it was used in the analysis, design, and optimization of ligand molecules in the ligand/receptor recognition process. 26 Similar analysis could be applied in the study of adsorbate−catalyst interactions, which makes it particularly useful for these catalytic systems where several interactions are found.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously applied this theory to understand the action mechanism of human dihydrofolate reductase inhibitors, , BACE1 inhibitors, , D2 dopamine receptor ligands, sphingosine kinase 1 (Sphk1) inhibitors, and HIV-1 protease flap fragments, among others.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous advantages to select such compounds: (a) they are compounds of great interest in medicinal chemistry, (b) reliable structural data are available for the molecular target (D2DR), [21] (c) data on biological activities are available for these ligands acting on D2DR, [22] (d) we have previously studied DA interacting in the active site of D2DR; [23] in addition, we have reported new ligands for this receptor, some of them very powerful and selective with respect to D1DR. [24][25][26] In other words, we have experience in this molecular target (e) the structural characteristic of these ligands allows to perform a systematic conformational study since their conformations are mainly determined by two dihedral angles (ϕ and ψ in Figure 1), (f) from a structural point of view they represent adequately ligands of complexes type (ii) since they are flexible but at the same time they have only three dihedral angles, being two of them the determinants of the spatial ordering, (g) structural differences between the ligands are convenient, in fact they are phenylethylamines with different hydroxylation patterns; note that PEA does not have hydroxyl groups in its structure, dopamine has two of them from its catechol ring, while m-OH-PEA has only one phenolic hydroxyl in meta position. The advantage of using structurally closely related compounds is that the effects of small structural changes on the properties of the compounds may then be determined.…”
mentioning
confidence: 99%